Monoclonal antibody cross-reactions between Drosophila and human brain. - Miller, C A (1983)
A panel of 146 monoclonal antibodies (MAbs), obtained with Drosophila melanogaster tissue as primary immunogen, was tested for cross-reactivity with the human central nervous system. Sites examined included spinal cord, cerebellum, hippocampus, and optic nerve. Nonnervous tissues tested were liver and lymph node. Approximately half of the antibodies reacted with one or more sites in the human central nervous system, identifying regional, cell class, and subcellular antigens. Some recognized neuronal, glial, or axonal subsets. Immunoblot analysis revealed that some antibodies reacted with similar antigen patterns in both species.